TRANSCRIPTOMIC ANALYSIS REVEAL BLOOD COAGULATION CASCADE IN THE INTESTINE OF DIABETES-INDUCED ZEBRAFISH (DANIO RERIO) DIETARY SUPPLEMENTED WITH TONGKA LANGIT BANANA (MUSA TROGLODYTARUM) - Yessica, Yustin
Diabetes Mellitus Type 2 (T2DM) is a metabolic disorder characterized by high blood sugar levels (hyperglycemia). Hyperglycemia increases blood coagulation which can lead to thrombosis and cardiovascular complications that can worsen the condition of T2DM patients. Carotenoids such as ?-carotene have been recognized as antioxidant agents and are likely to control hypercoagulation. One of the foods high in ?-carotene that has not been widely studied is tongka langit banana (Musa troglodytarum). This study aimed to determine the effect of tongka langit banana diet on the expression of genes that play a role in the blood coagulation cascade in the intestines of zebrafish induced diabetes (T2DM) through overfeeding. The study was conducted in silico using data from the total gut RNA sequencing of zebrafish intestines from the control group (NL), overfeeding+cavendish (OF), and overfeeding+tongka langit (OFTL). The quality of raw reads was analyzed using the FastQC v0.11.9 program and trimming the adapter and low quality sequence using the Cutadapt v2.8-2build1 program, so that clean readings were obtained. Clean reads were further aligned on the reference genome, Danio rerio GRCz11 obtained from ENSEMBL using the BWA v0.7.17 program. Reads that have been successfully mapped are then quantified using the HTSeq v0.11.2 program. Furthermore, differential gene expression analysis was carried out using the Deseq2 package (|L2FC|>1; padj<0.01) and an enrichment analysis using the DAVID program and Reactome database. Differential gene expression analysis showed 384 modulated genes in NL vs. OFTL. Tongka Langit banana diet (OFTL) is able to modulate the blood coagulation cascade by downregulate the expression of blood coagulation (f2, f5, f9a, f9b, f7, f7l, f10, fga, fgb, fgg, kng1) and their inhibitors (proca, serpina1, serpinc1, serpind1). This shows that tongka Langit can be a therapeutic agent to control blood coagulation disorders in patients with T2DM, so that it is expected to prolong their life expectancy.